Сучасні тенденції у туристичних WEB-виданнях - Свічкар, Є. С. (ХНУРЕ, 2023)
The paper discusses the achievements in the production and use of tourism web publications. The paper shows that tourism web publications are an important tool for providing users with access to information about services. The work also analyzed the shortcomings that can lead to user dissatisfaction and a negative impact on the reputation of travel brands. It was revealed that the development of tourism web publications in the future will depend on the dynamics of technological progress and changes in user behavior. In addition, it is necessary to improve the user experience and ensure the quality of the information provided.
Keywords: тенденції; туристичне видання